From Boss to Buddy: How Servant Leadership and Talent Management Make Employees Go the Extra Mile - Sari, Santi Retno; Sugiono, Edi; Nurwulandari, Andini (Indonesian Journal of Business, Accounting and Management, 2025)
This study aims to analyze the influence of servant leadership and talent management on employee thriving, and to test the moderating role of talent management in strengthening the relationship between servant leadership and thriving. Utilizing a quantitative approach with data collected from 143 employees across banking, commerce, and education sectors in Jakarta, this research employed PLS-SEM for data analysis. The findings indicate that both servant leadership and talent management have a significant positive effect on employee thriving. However, contrary to the hypothesis, talent management does not moderate the relationship between servant leadership and thriving. This suggests that while both are critical resources that independently contribute to employee growth and vitality, they operate through distinct mechanisms without a synergistic interaction. The results are discussed through the lens of Conservation of Resources (COR) Theory, highlighting the practical implications for leaders and HR practitioners to simultaneously yet independently develop both leadership quality and talent systems to foster a thriving workforce.